THE EFFECT OF PROFITABILITY, SIZE OF BOARD OF COMMISSIONER, AND FIRM SIZE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (An Empirical Study on Coal Sector Industry listed in the Indonesian Stock Exchange in 2012-2013) - Arina Nihaya Parahita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study tries to reveal the influence of profitability, board of commissioner, and size of the company on corporate social responsibility disclosure. The population of the research is 18 coal mining industry sub- sector listed on Indonesia Stocks Exchange on 2011 to 2013. The sampling method used in this study is saturated sampling method in which all of the population is the sample. The data analysis method of the study uses multiple regression. The results of the study found that the bigger profitability and the size of the company lead to larger corporate social responsibility disclosure. However, the larger the number board of commissioner leads to smaller corporate social responsibility disclosure. Furthermore, the government needs to regulate the implementation of CSRD which prioritize the public interest. There are several suggestion generated from the findings such as the company should implement corporate social responsibility based on their own awareness and report it to the public. The company should also balance the number of commissioner board and management. Thus, the board can function and communicate effectively in making decision related to the CSR. For the future research, it is expected to develop different measurement on corporate social responsibility to obtain a more valid and reliable results. As the current measurement may borne with many weaknesses and require improvement to reveal the best indicator of corporate social responsibility. Keywords: profitability, size board of commissioner, firm size, and corporate social responsibility disclosure